Effect of Polystyrene Nanoplastic on Colon, Liver, and Spleen Histopathology of Rats (Rattus norvegicus L.) - Diyah Utari; Alfiah Hayati; Inge Permatasari; Lina Afiifatul Abroroh; Nisrina Qatrunada; Rosida; Sasanaqia Maulidah; Mardhiah Hayati; Putri Ayu Ika Setiyowati; Dwi Winarni; Sugiharto; Firli Rahmah Primula Dewi; et al. (LenteraBio : Berkala Ilmiah Biologi, 2025)
Polystyrene, when exposed to ultraviolet light, can break down into nanoplastics (NPs), which enter the body and elevate reactive oxygen species, leading to oxidative stress which can damage cell structure and function by causing inflammation, necrosis, and tissue degeneration in target organs such as the colon, liver, and spleen. This study specifically investigates the impact of NPs on rats’ colons, livers, and spleens. The experimental design was completely randomized, comprising one control group and three treatment groups (n=6). The treatment groups were exposed to NPs concentrations of 1, 2, and 4 μL/kg, administered orally for 35 days. Tissue samples from the colon, liver, and spleen were collected, processed, and stained with H&E. Findings in the colon indicated an increase in submucosal and muscular thickness and a reduction in crypt length with higher NPs concentrations. In the liver, higher NPs concentrations resulted in a decrease in the percentage of normal and oedematous hepatocytes, along with an increase in necrotic hepatocytes, Kupffer cells, and the diameters of the portal and central veins. The spleen showed enlargement in the white pulp and germinal centre diameters, and increased thickness in the periarterial lymphoid sheath (PALS) and marginal zone. This study highlights the critical need to reduce NPs pollution to mitigate potential health risks.